Dynamic model development for lead acid storage battery - B. V. Rajanna; Malligunta Kiran Kumar (Institute of Advanced Engineering and Science, 2019)
It is widely accepted that electrochemical batteries ensure superior energy storage and reliability of power supply. This paper proposes to discuss the dynamic performance of the Lead Acid Storage battery and to develop an Electrical Equivalent circuit and study its response to sudden changes in the output. A detailed explanation of the discharging process for lead-acid storage batteries and the factors affecting the rate of chemical reactions is provided. The objective of the study is to find the reduction in terminal voltage due to the change in reaction rate and to evolve a simple dynamic model for discharge of the battery.